Dynamic Characteristics of Saturated Silty Soil Ground Treated by Stone Column Composite Foundation - Yongxiang Zhan; Guanlu Jiang; Hailin Yao (Advances in Materials Science and Engineering)
A shaking table model test was carried out to develop an understanding of the performance improvement of saturated silty soil ground using stone column composite foundation as reinforcement. It is found that at less than 0.161 g loading acceleration, soil between piles has not yet been liquefied, the response acceleration scarcely enlarges, and the shear displacement almost does not appear in silty soil. At 0.252 g loading acceleration, as a result of liquefaction of soil between piles, the response acceleration increases rapidly and reaches its peak, and the shear displacement of silty soil increases significantly. At 0.325 g loading acceleration, the integral rigidity of foundation decreases greatly, which reduces its capability of vibration transmission and result in the response acceleration amplification coefficient is less than that at the former loading acceleration, but the shear displacement of silty soil further increases. The stone column composite foundation can greatly reduce both the shear displacement and the settlement of ground compared with untreated foundation. Under the condition of 7-degree seismic fortification, the design meets seismic resistance requirements.